Biological shaping as a conservative alternative for crown lengthening: A review - Abdusalam Alrmali; Daniel Melker; Janet Zalucha; Hom‐Lay Wang (Wiley, 2024)
Abstract Objectives The perio‐restorative approach to maintaining supracrestal tissue attachment (STA; formerly known as biologic width) is a fundamental goal in modern dentistry. This article aims to review the clinical impact of biologic shaping (BS) as an innovative alternative to traditional crown lengthening procedures, reflecting over two decades of clinical experience. Material and Methods As a review paper, it is crucial to highlight that BS stands as a unique approach designed to optimize STA while emphasizing minimal to no removal of supporting bone. The review spans over two decades, consistently demonstrating clinical efficacy and predictability. Remarkably, BS focuses on addressing issues such as root concavities, developmental grooves, irregularities, furcation lips, and CEJ offering a remarkable level of clinical precision. Results The reviewed literature underscores that BS has consistently achieved substantial clinical success in fulfilling its objectives. This method presents a biologically sound alternative to traditional crown lengthening, placing a strong emphasis on the preservation of essential bone tissue and the establishment of durable STA. Conclusions The results suggest that BS is a logical and biologically driven approach for maintaining STA, making it a promising alternative to traditional crown lengthening. The method offers a predictable and reproducible way to preserve bone tissue while achieving durable STA. This innovation holds great promise in the field of periodontal and restorative dentistry.